Theologi Filsafat Politik Islam - Anton Anton (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: Humans, countries, religions, politics are parts that are difficult to separate, indeed the four are something of a link that connects one another. In short, to make a country better then of course it starts with a wise leader in attitude. The problem in this research is how political theology views in the Islamic world. The purpose of this study is to describe how the philosophical world of politics in Islam. This research uses descriptive qualitative methods, while the type of this research is library research. The conclusion of this research is that Islamic political theology can be said briefly how the mechanism and state rules are decorated with religious values. The politicians in taking various kinds of policies should be based on the interests of the people, the interests of the people, by the people and for the people. Meanwhile, philosophy is a science that is used to obtain rational truths. In this case it is very important to understand, Islam as the last religion brought by the prophet Muhammad PBUH taught the values of goodness, values of justice, values of caring, values of wisdom, values of beauty, values of togetherness. Equality and human dignity is more important than humans themselves. Islamic political philosophy should color a good lifestyle for politicians in carrying out their duties for the benefit of the people, carrying out the mandate of the people should be based on mature religious values so that later it will have a good impact on society in living as a nation, nation, religion, and community that lives in a country. Keywords: Theology, Philosophy, Islamic Politics. Abstrak: Manusia, negara, agama, politik merupakan bagian-bagian yang sulit untuk dipisahkan yang memang keempatnya merupakan sesuatu pertalian yang mengait antara satu sama lain. Singkat kata untuk menjadikan suatu negara menjadi yang lebih baik maka tentunya diawali dengan pemimpin yang bijak dalam bersikap. Masalah dalam penelitian ini adalah bagaimana pandangan teologi politik dalam dunia islam. Tujuan dari penelitian ini adalah untuk menjabarkan bagaimana filsafah dunia politik dalam Islam. Penelitian ini menggunakan Metode metode deskriptif kualitatif, sedangkan jenis penelitian ini merupakan penelitian pustaka (Library Research). Kesimpulan dari penelitian ini adalah Theologi politik Islam dapat dikatakan secara singkat bahwa bagaimana mekanisme dan aturan bernegara ini dihiasi dengan nilai-nilai agama. Para politisi dalam mengambil berbagai macam kebijakkan hendaklah didasari atas kepentingan rakyat, kepentingan dari rakyat, oleh rakyat dan untuk rakyat. Sementara itu, filsafat adalah sebuah ilmu yang digunakan untuk memperoleh kebenaran rasional. Dalam hal ini sangat penting dipahami, Islam sebagai agama yang terakhir dibawa oleh nabi Muhammad Saw telah mengajarkan nilai-nilai kebaikan, nilai-nilai keadilan, nilai-nilai kepedulian, nilai-nilai kearifan, nilai-nilai keindahan, nilai-nilai kebersamaan. Persamaan derajat dan martabat manusia lebih penting dari manusia itu sendiri. Filsafat politik Islam hendaknya mewarnai pola hidup yang baik bagi para politisi dalam menjalankan tugas untuk kepantingan rakyat, mengemban amanah rakyat hendaklah didasari oleh nilai-nilai keberagamaan yang matang sehingga nantinya memberikan dampak yang baik bagi masyarakat dalam hidup bernegara, berbangsa, beragama, bermasyarakat yang hidup di negara.Kata Kunci: Theologi, Filsafat, Politik Islam.